In silico Approaches for Effective and Potential Biocontrol Agents against Targeting Chitin Synthase Protein of Pathogenic Fungus Alternaria alternata (Fr.) Keissl. of Onion (Plant Tissue Culture and Biotechnology, 2026)
This study utilized an in silico drug discovery approach, combining molecular docking and molecular dynamics (MD) simulations, to identify novel inhibitors of the fungal virulence factor, Chitin Synthase, an enzyme essential for A. alternata's survival and hyphal growth. The leaf blight-associated fungus from onion was identified as A. alternata based on its woolly greyish-brown mycelia, pale cylindrical conidia, and shorter conidiophores. Molecular identification using 18S ITS1 and ITS2 sequencing (566 bp) confirmed 100% similarity with A. alternata in GenBank. The sequence was submitted to NCBI under accession number PP894981.1 (JUF0089). A library of 105 phytocompounds was virtually screened, yielding 26 candidates with binding affinities superior to those of the reference inhibitor. Among these, 10 complied with Lipinski’s rule of five, indicating favorable drug-likeness. The two most promising candidates, luteolin and azadiradione, were selected as lead compounds for further validation. A 200 ns MD simulation was performed, and subsequent analysis of Root Mean Square Deviation (RMSD), Root Mean Square Fluctuation (RMSF), and hydrogen bond interactions confirmed stable protein-ligand complexes throughout the trajectory, with binding free energies supporting strong inhibitory potential. These results strongly suggest that luteolin and azadiradione act as effective inhibitors by specifically targeting the active site of the Chitin Synthase protein. This research validates these natural compounds as potent starting points for the rational design and development of new antifungal drugs against A. alternata. To our knowledge, this is the first in silico investigation of phytocompound-based control strategies against A. alternata conducted in Bangladesh.Plant Tissue Cult. & Biotech. 35(2): 347-359, 2025 (December)